SCIENTIFIC ARTICLE PLAGIARISM DETECTION USING THE QUADWORD APPROACH - Hari Purwanto; Betesda Sinaga; Iswandir Iswandir; Mohamad Adila Rossa; Abdul Jamil (Jurnal Ilmiah METADATA, 2026)
Plagiarism is defined as the act of taking or presenting another person's work as one's own, regardless of intent. This infraction can be substantiated when supported by robust evidence. Academic works are often targeted by plagiarism, as the constrained writing proficiency among undergraduate students may foster such occurrences. A principal preventive endeavor to mitigate plagiarism within academic works involves the deployment of plagiarism detection applications. A primary preventive measure to mitigate plagiarism in academic works is the utilization of plagiarism detection software. Third-party applications typically require the purchase of a license to optimally access their full features. Cognizant of this limitation, the author developed an alternative application, although its capabilities are restricted to the detection of internal manuscripts. The application engineered herein implements the Rabin-Karp algorithm, leveraging a quadword approach. The concept of the quadword itself incorporates a phrase-based technique, functioning by generating a collection or set comprising four consecutive words within the source text